A STUDY OF IMAMI AND SUNNI JURIS PRUDENTIAL OPINIONS ABOUT THE RULING OF TAWAF OF CHILDREN IN HAJJ - Ravandmahin; Ahmarihosein (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The issues that children have to deal with during Hajj are very delicate and precise, and the lack of knowledge about performing Hajj causes children many problems. Tawaf is one of the issues of Hajj that has conditions, such as intention, purification from hadith, purity of clothing, circumcision, and mawlawat The Hajj of a child is not different from the rules of Hajj of an adult in terms of its rules, only in the part where the child is not able to perform Tawaf and Hajj, in which the components of Tawaf are performed by the child. This study seeks to investigate whether, according to Imami and Sunni jurists, these conditions of Hajj and its rulings can be performed by the child alone or should the guardian perform them on his behalf. In order to study these issues from the point of view of jurists, these matters have been mentioned. In examining the topics, it can be concluded that the child is divided into categories of discriminators, non-discriminators and affiliates. Each of these types has either common rules or separate rules, but what can be said in the discussion of Tawaf, if the child can perform Hajj from the mentioned acts, then he will do it; But if he is not able to do it, his guardian must teach him to perform Hajj or perform it on behalf of the child.